Ghrelin Improves Functional Survival of Engrafted Adipose-Derived Mesenchymal Stem Cells in Ischemic Heart through PI3K/Akt Signaling Pathway - Han, Dong (Biomed Res Int, 2015)
Mesenchymal stem cells (MSCs) have been proposed as a promising cell population for cell therapy and regenerative medicine applications. However, the low retention and poor survival of engrafted cells hampered the therapeutic efficacy of engrafted MSCs. Ghrelin is a 28-amino-acid peptide hormone and is proved to exert a protective effect on the cardiovascular system. This study is designed to investigate the protective effects of ghrelin on engrafted adipose-derived mesenchymal stem cells (ADMSCs) and its beneficial effects with cellular therapy in mice myocardial infarction (MI). Results showed that intramyocardial injection of ADMSCs combining with ghrelin administration inhibited host cardiomyocyte apoptosis, reduced fibrosis, and improved cardiac function. To reveal possible mechanisms, ADMSCs were subjected to hypoxia/serum deprivation (H/SD) injury to simulate ischemic conditions in vivo. Ghrelin (10(−8) M, 33712 pg/ml) improved ADMSCs survival under H/SD condition. Western blot assay revealed that ghrelin increased AKT phosphorylation both in vivo and in vitro, decreased the proapoptotic protein Bax, and increased the antiapoptotic protein Bcl-2 in vitro, while these effects were abolished by PI3K inhibitor LY294002. These revealed that ghrelin may serve as a promising candidate for hormone-driven approaches to improve the efficacy of mesenchymal stem cell-based therapy for cardiac ischemic disease via PI3K/AKT pathway.